2009
DOI: 10.1111/j.1365-2915.2008.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of New World screwworm fly, Cochliomyia hominivorax, suggests genetic isolation of some Caribbean island populations following colonization from South America

Abstract: . Larval infestations of the New World screwworm (NWS) fly, Cochliomyia hominivorax , cause considerable economic losses through the direct mortality and reduced production of livestock. Since the 1950s, NWS populations in North and Central America have been the target of virtually continuous eradication attempts by sterile insect technique (SIT). Nevertheless, in some areas, such as Jamaica, SIT-based control programmes have failed. Reasons for the failure of SIT-based programmes in some locations are unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
(45 reference statements)
0
17
0
2
Order By: Relevance
“…The SIT program in Jamaica in 1999-2005 failed because the sterile flies originated from Mexico. This failure might be a result of mating incompatibility between the sterile and the wild flies or the existence of sexually incompatible cryptic species (McDonagh et al 2009). Comparisons of the genetic variation within and between populations of target species should be investigated in order to infer the genetic similarity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The SIT program in Jamaica in 1999-2005 failed because the sterile flies originated from Mexico. This failure might be a result of mating incompatibility between the sterile and the wild flies or the existence of sexually incompatible cryptic species (McDonagh et al 2009). Comparisons of the genetic variation within and between populations of target species should be investigated in order to infer the genetic similarity.…”
Section: Discussionmentioning
confidence: 97%
“…In italics, the proportions of individuals derived from the source population. Values of m above 0.1000 are in bold Table 6 Tests of the demographic contraction in each population based on mode-shift distortion in allele frequency distributions and heterozygosity excess with three underlying mutation models (IAM, SMM, and TPM) performed using BOTTLENECK (Cornuet and Luikart 1996) Population Probability values were determined using one-tailed Wilcoxon tests NS refers to no significant value a A shift in the distribution at allelic frequency classes is expected in bottleneck populations b Parameters for the TPM model included 90% signal step mutation and 10% multi-step mutation that caused failure of the control program (Macleod and Donnelly 1961;McDonagh et al 2009). If the level of sterility is insufficient, the trapping survey and the fruit sampling would reveal the expansion of the fruit fly population size and a higher fruit damage level, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity patterns of C. hominivorax populations have been extensively investigated through nuclear and mitochondrial markers, restriction fragment length polymorphism (RFLP) analyses and sequence data (Roehrdanz 1989;Taylor et al 1996a,b,c;Lyra et al 2005Lyra et al , 2009Torres et al 2007;McDonagh et al 2009;Torres and AzeredoÐEspin 2009;Fresia et al 2011). The majority of genetic studies have suggested low differentiation among C. hominivorax populations.…”
Section: Discussionmentioning
confidence: 99%
“…These results and some recent molecular studies suggesting signiÞcant genetic differentiation in C. hominivorax populations, speciÞcally in the Caribbean and south of the Amazon basin (McDonagh et al 2009, Fresia et al 2011, prompted us to conduct crossing studies to evaluate mating competitiveness, mating preference, and reproductive compatibility between two screwworm strains.…”
mentioning
confidence: 99%
“…The aim of this study was to prove a fast and user-friendly protocol of DNA isolation, that will allow to study the genetic variability and molecular taxonomy of the species in Ecuador. In order to contribute to an efficient biological control method with more genetic information based on a large number of samples in a short period of time (Klassen and Curtis, 2005;McDonagh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%